THE FAMILY EFFECT: EVIDENCE FROM SMALL RETAIL STORES IN INDIA - Fazal, Faraz (2007)
Research into family firms is usually associated with family succession problems but very few studies have adapted a strategic management perspective. Decision-making made by family firms are distinct from patterns in other firms such that a Ã¢ÂÂfamily effect occurs in the process. This study examines for the existence of family effect and what implications it might have for the competitive choices of family firms. Through a series of interviews with owner-manager in seven small retail stores in India, it is found that the family effect pushes firms to be more market oriented than entrepreneurially oriented and more risk averse. Worse still, this is exacerbated when human capital is low. Conclusions and implications for various stakeholders of these findings are drawn and discussed.